A plant design of an avocado oil extraction plant - Adamos, Annette Christie R. (College of Engineering, 1994)
Product: Crude avocado oil -- Plant site: Silang, Cavite -- Annual plant production: 149,205 kg -- Proposed selling price: P 450.00 per kg of oil -- Prevailing market price: Oil - P 1,131.35, Extract - P 450.00 - P 1,800.00 -- Annual gross sales: P 67,142,250.00 -- Annual net income: P 17,595,251.02 -- Total capital investment: P 33,391,792.66 -- Total production cost: P 35,150,884.51 -- Rate of returns: 96.70% before taxes, 53.19% after taxes -- Breakeven sales: P 10,769,877.00 -- Breakeven capacity: 16.04% -- Payback period: 0.93 year before taxes, 1.69 years after taxes